Glow discharge optical emission spectrometry for quantitative depth profiling of CIGS thin-films. Issue 6 (30th April 2019) - Kodalle, Tim; Greiner, Dieter; Brackmann, Varvara; Prietzel, Karsten; Scheu, Anja; Bertram, Tobias; Reyes-Figueroa, Pablo; Unold, Thomas; Abou-Ras, Daniel; Schlatmann, Rutger; Kaufmann, Christian A.; Hoffmann, Volker
Abstract : The article demonstrates how quantitative compositional depth profiles of Cu(In, Ga)(S, Se)2 layers can be utilized to determine their energy bandgap distribution. Abstract : Determining elemental distributions dependent on the thickness of a sample is of utmost importance for process optimization in different fields e.g. from quality control in the steel industry to controlling doping profiles in semiconductor labs. Glow discharge optical emission spectrometry (GD-OES) is a widely used tool for fast measurements of depth profiles. In order to be able to draw profound conclusions from GD-OES profiles, one has to optimize the measurement conditions for the given application as well as to ensure the suitability of the used emission lines. Furthermore a quantification algorithm has to be implemented to convert the measured properties (intensity of the emission lines versus sputtering time) to more useful parameters, e.g. the molar fractions versus sample depth (depth profiles). In this contribution a typical optimization procedure of the sputtering parameters is adapted to the case of polycrystalline Cu(In, Ga)(S, Se)2 thin films, which are used as absorber layers in solar cell devices, for the first time. All emission lines used are shown to be suitable for the quantification of the depth profiles and a quantification routine based on the assumption of constant emission yield is used. The accuracy of this quantification method is demonstrated on the basis of several examples. The bandgap energy profile of the compound semiconductor, as determined by the elemental distributions, is compared to optical measurements. The depth profiles of Na – the main dopant in these compounds – are correlated with measurements of the open-circuit voltage of the corresponding devices, and the quantification of the sample depth is validated by comparison with profilometry and X-ray fluorescence measurements.